Effect of Soy protein-based edible coatings with antioxidant activity and modified atmosphere packaging on the quality of fresh-cut produces - Ghidelli, Christian (2020)
The market demand for fresh-cut fruits and vegetables has experienced a rapid expansion due to the increased health consciousness of consumers, busy lifestyles, and purchase power. However, the shelf life of fresh-cut products is greatly reduced because of the rapid metabolism of the wound tissue, requiring the use of different technologies to maintain their quality and extend the shelf life. The objective of the present work was to develop a soy protein-based edible coating with antioxidant activity and to evaluate the combined effect of selected edible coatings and modified atmosphere packaging (MAP) conditions on the quality and shelf life of fresh-cut ‘Blanca de Tudela’ artichoke, ‘Telma’ eggplant, and ‘Rojo Brillante’ persimmon during storage at 5 ºC, which are characterized by a relatively short shelf life due to a rapid onset of enzymatic browning. Firstly, the effect of ascorbic acid (AA), citric acid (CA), peracetic acid (PA), calcium chloride (CaCl2), cyclodextrin (CD), cysteine (Cys), hexametaphosphate (HMP), and 4-hexylresorcinol (Hexyl) at different concentrations was studied as a pre-screening at controlling enzymatic browning in extracts and precipitates (in vitro studies). Then, the most effective antioxidants type and concentration were selected to be tested in fresh-cut tissue of artichoke, eggplant and persimmon stored at 5 ºC (in vivo studies). Among the different antioxidants tested, Cys was the most effective to control enzymatic browning of fresh-cut artichokes and eggplants. The maximum commercial shelf-life was 4 and 9 days of storage at 5 ºC for fresh-cut artichokes and eggplants when Cys was applied at concentrations of 0.5% and 1%, respectively. In fresh-cut ‘Rojo Brillante’ persimmon, application of 1.12% AA and 0.21% CA extended the limit of marketability in the range of 5-7 days of storage at 5 ºC; whereas, CaCl2 contributed in a lower extend. Soy protein isolate (SPI)-based edible coatings were prepared with the most effective antioxidant agents from in vivo studies to reduce enzymatic browning and extend shelf of selected produces. In fresh-cut artichokes, the optimization of the SPI:Beeswax (BW) edible coating was based on BW and Cys content. An increase in the BW content from 20 to 40% (dry basis) allowed to reduce Cys concentration from 0.5% to 0.3%, Summary diminishing the yellow color provided by Cys application to artichoke tissue. This coating contributed to the control of enzymatic browning and improved the quality of fresh-cut ‘Blanca de Tudela’ artichokes, reaching 4 days of commercial shelf life at 5 ºC without off-odors. The application of Cys, either alone or incorporated to the SPI-BW coating, helped at controlling enzymatic browning and extending the commercial shelf life of fresh-cut eggplants. The visual assessment evaluated the samples coated with the SPI-BW-1% Cys coating as significantly less brown than the rest of the treatments, reaching the maximum commercial shelf life of 9 days at 5 ºC. For fresh-cut persimmon, the formulated SPI edible coating contained 1% CA and 0.3% CaCl2. The application of this coating did not affect negatively the overall sensory quality of the product, which makes this coating a potential treatment to extend the commercial shelf life of minimally processed ‘Rojo Brillante’ persimmon. Finally, the combination of selected SPI-based edible coatings with antioxidant capacity and MAP were evaluated on fresh-cut ‘Blanca de Tudela’ artichoke, ‘Telma’ eggplant, and ‘Rojo Brillante’ persimmon. MAP conditions included active conventional MAP (5 kPa O2 + 15 kPa CO2), passive MAP, and high O2 MAP (>50 kPa) and they were compared to atmospheric conditions as control. ‘Telma’ eggplants and ‘Blanca de Tudela’ artichokes were susceptible to tissue damage when packaged under active or passive MAP with low O2 and high CO2 levels, whereas high O2 MAP (>30-50 kPa) resulted detrimental for the storage of fresh-cut ‘Rojo Brillante’ persimmons. The combination of the optimized coating with the different MAP did not extend the shelf life of artichoke slices, but helped maintain the antioxidant capacity of the product as compared to control packaging conditions. Similarly, the SPICys coating in atmospheric conditions packaging provided the best and cheapest approach for extending the shelf life of fresh-cut eggplants up to 9 days of storage. On the contrary, the combination of the SPI-based coating with the active MAP packaging (5 kPa O2 + 15 kPa CO2) showed a synergic effect in controlling tissue browning of fresh-cut ‘Rojo Brillante’ persimmon, maintaining the visual quality above the limit of marketability up to 8-10 days of storage at 5 ºC.